E-MONEY FROM THE TECHNOLOGICAL POINT OF VIEW - N. N. Kolosovskaya (Финансы: теория и практика, 2017)
The article analyzes electronic money, in particular, crypto currency in the context of civil law. Applying historical method, the author presents a brief genesis of the creation and development of electronic contracts, as they were a real basis of emergence and use of electronic money. The views of Russian civil lawyers regarding the concept of electronic money are considered, and the author’s definition of this legal category is suggested. The author argues that electronic money is an account pertaining to the right or duty of an empowered particular entity to use the existing set of data on the kind and amount of payment units belonging to the an entity to pay for goods, works or services via electronic systems of non-bank credit organizations, i. e. without opening a bank account. The trend towards expanding the scope of non-cash payments, bypassing the existing banking system is revealed. The analysis of the legal regime of crypto currency circulation allows concluding that this type of electronic algorithms has been developed in order to create an unofficial payment system that does not have a single coordinating center but rather controlled by all users regardless of their location, and, therefore, cannot be “blocked”. In Russia, the crypto currency is not officially recognized, nevertheless officials believe that this means of payment should be used, since the available foreign experience attest to its effectiveness, notably, unlimited possibilities of transactions, free and instantaneous (0.01 seconds) international transfers, simplicity of use, etc. However, in order to avoid negative consequences, it is necessary to identify the market segments in which bitcoins will be used. The civil law of the Russian Federation considers crypto currency as an informal payment means for which it is necessary to develop in the very near future an appropriate legal regime. The future legislation should also pay attention to the Internet sites that accept bitcoins as a means of payment, and define the legal status of subjects involved in civil circulation. The suggested definition of electronic money, Bitcoin concept refinement and the arguments in support of recognition of electronic money as an informal payment unit contribute to the creation of a legal platform for use of a new universal object in civil transactions in Russia through IT-technologies.